Germination of fresh horse purslane (Trianthema portulacastrum) seeds in response to different environmental factors - Lee, Jihyun; Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2011)
Horse purslane, a C4 species, is a branched, prostrate, and annual weed of upland field crops throughout the tropics. Experiments were conducted to determine the influence of various environmental factors on seed germination and seedling emergence of two populations of horse purslane. Seeds were collected from rice fields of the International Rice Research Institute (the IR population) and from sorghum fields of the University of the Philippines (the UP population); the two sites were 5 km apart in Los Baños, Philippines. Germination response of both populations was greater at 30/20 C and35/25 C day/night temperatures than they were at 25/15 C alternating day/night temperatures. Germination of both populations was greater in the light/dark regime than in darkness. In dark, depending on the temperature, seed germination of the UP population ranged from 37 to 62%, whereas seed germination of the IR population was < 20%. Exposure to 5 min at 117 and 119 C for the IR and UP populations, respectively, reduced germination to 50% of maximum germination. Osmotic potential of −0.26 MPa inhibited germination to 50% of the maximum for the UP population, whereas the corresponding value for the IR population was −0.37 MPa. Seeds placed on or near the soil surface had maximum emergence, and emergence declined with increase in seed burial depth. Seedling emergence of the UP and IR populations was 74% and 13%, respectively, for seeds placed on the soil surface. For both populations, no seedlings emerged from a soil burial depth of 6 cm or more. Germination and emergence responses to light and seed burial depth differed between the two populations of horse purslane. Residues on the soil surface of up to 6 Mg ha−1 did not influence seedling emergence of either populations. Knowledge gained in this study could contribute to developing components of integrated weed management strategies for horse purslane.